KEPRIBADIAN TOKOH UTAMA DALAM NOVEL AWAN-AWAN DI ATAS KEPALA KITA KARYA MIRANDA MALONKA - Mutia Rahmawati; Dicky Rachmat Pauji; Kurnia Rachmawati (Universitas Negeri Makassar, 2023)
This study aims to describe and analyze the main character's personality structure, namely the id, ego, and superego. This study uses a descriptive-qualitative approach to produce data in the form of words and sentences that can be described structurally according to the theory of literary psychology. The source of the data used is the novel Awan-Awan di Atas Kepala Kita using library techniques, notes, and documents. The results of the research show that the id, ego, and superego are the main characters personality components, Ben and Kay. In the two main characters, aspects of Ben's ego personality appear due to the urge of the id trying to control himself, and aspects of Ben's superego are controlled by conscience. Meanwhile, aspects of Kay's ego personality emerged because of the id drive, which overshadowed realistic principles, and Kay's superego aspects were controlled by the existence of ego drives. The strongest aspect of Ben's personality, is the controlling ego, and in Kay's personality, the id aspect dominates.